2001
DOI: 10.1523/jneurosci.21-09-03261.2001
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Feeding in the Nucleus Accumbens Shell: Rostrocaudal Segregation of GABA-Elicited Defensive Behavior Versus Eating Behavior

Abstract: This study examined localization of positive versus negative motivational functions mediated by GABA circuits within the accumbens shell. Microinjections of a GABA A agonist (0, 25, 75, and 225 ng/0.5 l muscimol) in rostral shell sites elicited appetitive increases in eating behavior. In contrast, microinjections in caudal shell sites elicited defensive burying or pawtreading behavior. Rats whose microinjections landed bilaterally outside of the accumbens shell did not display either behavior. Defensive tread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(199 citation statements)
references
References 73 publications
17
180
1
1
Order By: Relevance
“…This was accompanied at times by hind limb movements which pushed bedding back behind the rat as it progressed forwards. This pattern of behavior has been previously described for increases of spontaneous burying behavior induced by muscimol injected into the nucleus accumbens (Reynolds and Berridge 2001). Grooming was defined as licking of the forelimbs and body and/or paw strokes of the face and body.…”
Section: Behavioral Testingmentioning
confidence: 55%
See 1 more Smart Citation
“…This was accompanied at times by hind limb movements which pushed bedding back behind the rat as it progressed forwards. This pattern of behavior has been previously described for increases of spontaneous burying behavior induced by muscimol injected into the nucleus accumbens (Reynolds and Berridge 2001). Grooming was defined as licking of the forelimbs and body and/or paw strokes of the face and body.…”
Section: Behavioral Testingmentioning
confidence: 55%
“…CRF administration, though this response has been previously reported in mice (Litvin et al 2007) and rats (Korte et al 1993;Price et al 1998;Wiersma et al 1995) and could only be seen if bedding material were present. Although the burying response evoked by CRF appeared almost identical to behaviors directed towards the electrified probe in the defensive burying response, the occurrence of burying in the absence of a specific aversive stimulus made the behavior appear spontaneous as reported following muscimol injected into the nucleus accumbens (Reynolds and Berridge, 2001). Bedding was pushed or sprayed in front of the rat by vigorous and repetitive movement of the forelimbs, and the formation of multiple elevated mounds of bedding distinguished the behavior from nest building or burrowing.…”
Section: Characterization Of Crf-evoked Behaviorsmentioning
confidence: 73%
“…4). This falls within the same rostral half where appetitive food intake, conditioned place preference effects are best produced by microinjections of AMPA/kainate glutamate receptor antagonist (DNQX) or by GABA A agonist (muscimol) (Reynolds and Berridge, 2001, although our opioid hot spot here was even more anatomically restricted.…”
Section: Hedonic Hot Spot For "Liking" Enhancementmentioning
confidence: 92%
“…Therefore, DA-mediated plasticity may be relatively preserved in NAc shell compared with DMS after METH-induced neurotoxicity, allowing DA-mediated synaptic modifications there to subserve consolidation of response-reversal learning. Furthermore, studies have shown that there are differences in how rostral and caudal NAc shell modulate behavior (Reynolds and Berridge, 2001). Our infusions targeted the rostral NAc shell, and given the differences in behavioral output of rostral and caudal NAc shell, as well as the anatomical inputs/outputs to the two regions (eg, Groenewegen et al, 1999;Usuda et al, 1998), it will be interesting in future studies to examine the relative contributions of the rostral vs caudal NAc shell to reversal learning in normal and METH-pretreated rats.…”
Section: Discussionmentioning
confidence: 99%